Managing Vulnerability and Boosting Productivity in Agriculture through Weather Risk Mapping : A Guide for Development Practitioners - Arce, Carlos (World Bank, Washington, DC, 2015)
Productivity in the agricultural sector is inherently dependent on weather, such as variations in rainfall and temperature. As a result, weather risk events can cause losses in yield and production that translate into economic losses for producers, as well as other sector stakeholders that depend on income from agricultural trade, transport, processing, or export. This document is a guide for development practitioners and strategically presents a variety of mapping techniques for agricultural risk management and illustrates the application of these techniques for informing public and private sector development strategies. The introduction places weather risk mapping within the broader context of agricultural risk, explaining how mapping can enable risk identification, assessment and management activities, and each chapter elaborates on one or more of the technical components. A basic definition of agro-meteorology is provided, along with a discussion of different mapping techniques. The guide presents the available remote (satellite) databases of agro-meteorological variables that can be used for the purpose of weather risk mapping, assessing the advantages and drawbacks of each database and their suitability for different purposes. The document reviews current risk mapping analyses based on historical weather observations, which are typically used for risk identification and assessment, including climatologies, hazard and risk maps, climate regionalizations and agro-ecological zones (AEZ). The document also reviews forward-looking mapping techniques, known as diagnostic and forecasting analyses, specific examples of which are drawn from the United States, the European Union, and Australia. Finally, the guide provides instruction on how and why to conduct agro-ecological zoning, a technique that can be used to assess land-use types, land resources, land suitability, and climatic and agro-climatic regionalizations, as well as to inform land use recommendations. The concluding chapter demonstrates a step-by-step application of agro-ecological zoning in a case study of Mozambique.